Antibiotic resistance of bacterial agents isolated in a neonatal intensive care unit in eastern Turkey - Taskin, E; Kilic, M; Aygun, AD; Akarsu, S; Kurt, AN (Oxford Univ Press, 2004)
[Abstract Not Available]
Keywords: Meningitis; Sepsis; Septicemia